2020
DOI: 10.1155/2020/8812188
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behavior Evolution and Damage Characterization of Coal under Different Cyclic Engineering Loading

Abstract: The cyclic loading causes the strength change of porous rocks, which can be frequently encountered in underground coal mining. In order to quantify the cumulative damage of porous coal, multilevel uniaxial cyclic compressive tests were carried out considering different loading frequencies. The results show that under cyclic loading, Young’s modulus of coal shows a first drastic increase and then decrease trend in terms of the number of loading-unloading cycles, while the Poisson’s ratio gradually increased at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Although the mechanical properties of briquette and raw coal are not exactly the same, there are great similarities in the mechanical laws of briquette coal [35]. Briquette is favored by many scholars because of its good repeatability [36][37][38][39]. This paper also conducts a series of experiments on briquette coal.…”
Section: Preparation Of Briquette With Different Moisture Contentmentioning
confidence: 99%
“…Although the mechanical properties of briquette and raw coal are not exactly the same, there are great similarities in the mechanical laws of briquette coal [35]. Briquette is favored by many scholars because of its good repeatability [36][37][38][39]. This paper also conducts a series of experiments on briquette coal.…”
Section: Preparation Of Briquette With Different Moisture Contentmentioning
confidence: 99%
“…M. Zhang pointed out that increasing the loading and unloading rate will reduce the total acoustic emission ring of red sandstone samples, and the total acoustic emission count of rock samples has a negative linear relationship with the loading and unloading rate [5]. H. Wang proposed that the loading/unloading response ratio (LURR) can be used to evaluate the damage of coal and rock under cyclic load [6]. T. Wang studied the variation characteristics of acoustic emission energy rate of red sandstone under cyclic loading and unloading.…”
Section: Introductionmentioning
confidence: 99%
“…The results of these tests have shown that the confining pressure and the amplitude, frequency, and peak value of the axial stress are important factors affecting the mechanical behaviour of rocks [14,26,30]. Wang suggested that the damage time for coal would be delayed by an increase in frequency and that the peak stress of loading had the most significant influence on coal damage [31]. Taheri performed cyclic loading experiments on lignite and observed that, with an increase in confining pressure, the specimen damage under axial loading decreased [32].…”
Section: Introductionmentioning
confidence: 99%